Targeting the thioredoxin system as a novel strategy against B‐cell acute lymphoblastic leukemia. Issue 5 (5th April 2019) - Fidyt, Klaudyna; Pastorczak, Agata; Goral, Agnieszka; Szczygiel, Kacper; Fendler, Wojciech; Muchowicz, Angelika; Bartlomiejczyk, Marcin Adam; Madzio, Joanna; Cyran, Julia; Graczyk‐Jarzynka, Agnieszka; Jansen, Eugene; Patkowska, Elzbieta; et al.
Abstract : B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL) is a genetically heterogeneous blood cancer characterized by abnormal expansion of immature B cells. Although intensive chemotherapy provides high cure rates in a majority of patients, subtypes harboring certain genetic lesions, such as MLL rearrangements or BCR‐ABL1 fusion, remain clinically challenging, necessitating a search for other therapeutic approaches. Herein, we aimed to validate antioxidant enzymes of the thioredoxin system as potential therapeutic targets in BCP‐ALL. We observed oxidative stress along with aberrant expression of the enzymes associated with the activity of thioredoxin antioxidant system in BCP‐ALL cells. Moreover, we found that auranofin and adenanthin, inhibitors of the thioredoxin system antioxidant enzymes, effectively kill BCP‐ALL cell lines and pediatric and adult BCP‐ALL primary cells, including primary cells cocultured with bone marrow‐derived stem cells. Furthermore, auranofin delayed the progression of leukemia in MLL ‐rearranged patient‐derived xenograft model and prolonged the survival of leukemic NSG mice. Our results unveil the thioredoxin system as a novel target for BCP‐ALL therapy, and indicate that further studies assessing the anticancer efficacy of combinations of thioredoxin system inhibitors with conventional anti‐BCP‐ALL drugs should be continued. Abstract : In B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL), we observed oxidative stress along with increased expression of the enzymes of the thioredoxin antioxidant system. Inhibition of these enzymes with auranofin and adenanthin triggered oxidative and endoplasmic reticulum stress and effectively killed BCP‐ALL cells in vitro and in vivo . Our results unveil thioredoxin system as a novel target for BCP‐ALL therapy.